2008
DOI: 10.1074/jbc.m708178200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Gic2 Localization and Function by Phosphatidylinositol 4,5-Bisphosphate during the Establishment of Cell Polarity in Budding Yeast

Abstract: Establishment of cell polarity is important for a wide range of biological processes, from asymmetric cell growth in budding yeast to neurite formation in neurons. In the yeast Saccharomyces cerevisiae, the small GTPase Cdc42 controls polarized actin organization and exocytosis toward the bud. Gic2, a Cdc42 effector, is targeted to the bud tip and plays an important role in early bud formation. The GTP-bound Cdc42 interacts with Gic2 through the Cdc42/Rac interactive binding domain located at the N terminus of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 32 publications
0
31
0
Order By: Relevance
“…As mentioned earlier, in many cell types, membrane phosphoinositides have been linked to actin filament dynamics and function via the action of small Rho and Rac family GTPases. Likewise, in the same way, PtdIns(4,5)P 2 plays an essential role in proper actin cytoskeleton organization during polarized growth in S. cerevisiae (20). Moreover, it has been reported that Ste5 is transported to the shmoo tip on actin cables (21).…”
Section: Stable Anchoring Of Ste5 At the Projection Tip Does Not Requmentioning
confidence: 99%
“…As mentioned earlier, in many cell types, membrane phosphoinositides have been linked to actin filament dynamics and function via the action of small Rho and Rac family GTPases. Likewise, in the same way, PtdIns(4,5)P 2 plays an essential role in proper actin cytoskeleton organization during polarized growth in S. cerevisiae (20). Moreover, it has been reported that Ste5 is transported to the shmoo tip on actin cables (21).…”
Section: Stable Anchoring Of Ste5 At the Projection Tip Does Not Requmentioning
confidence: 99%
“…Interestingly, swapping the amino terminus of Sec3 with the amino terminus of Gic2, a known downstream effector of Cdc42 that contains the well-characterized CRIB (Cdc42/ Rac Interaction/Binding) domain and a polybasic region, completely replaces the fulllength Sec3 function in yeast cells Orlando et al 2008). It is possible that the binding of Cdc42 and PI(4,5)P 2 to Sec3 helps recruit Sec3 to the bud tip.…”
Section: The Rho Family Of Small Gtp-binding Proteinsmentioning
confidence: 99%
“…It is now well established that polybasic domains in proteins function as interaction modules with phosphatidylinositol 3,4,5-trisphosphate (PtdIns 3,4,5-P 3 ), which has not been detected in plant cells to date, and with phosphatidylinositol 4,5-bisphosphate (PtdIns 4,5-P 2 ; Fig. 1B; Papayannopoulos et al, 2005;Heo et al, 2006;Kaadige and Ayer, 2006;Sun et al, 2007;Orlando et al, 2008). Importantly, it has been specifically demonstrated that the polybasic domains of Rho proteins and other small GTPases interact with both PtdIns 4,5-P 2 and PtdIns 3,4,5-P 3 (Heo et al, 2006).…”
Section: The Polybasic Domain a Prenylation And Membrane-binding Modulementioning
confidence: 99%